2017
DOI: 10.4274/tjo.34735
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Aflibercept Treatment Responses in Eyes with Bevacizumab/Ranibizumab-resistant Wet Age-related Macular Degeneration

Abstract: Objectives:To evaluate anatomic and functional results after switching from intravitreal bevacizumab or ranibizumab treatment to aflibercept for wet (neovascular) age-related macular degeneration.Materials and Methods:This retrospective study included 22 eyes of 22 patients resistant to treatment with at least 6 injections of bevacizumab or ranibizumab. The first three injections had been applied monthly, the others pro re nata (PRN). Outcome measures were follow-up period, injection number, best corrected vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
10
0
1
Order By: Relevance
“…This was especially important for the treatment of anti-VEGF unresponsive eyes and those with tachyphylaxis. Numerous investigators have evaluated its efficacy in these circumstances and all demonstrated some benefit [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Two meta-analyses attempted to evaluate the pooled data from these numerous studies.…”
Section: Exudative Age-related Macular Degenerationmentioning
confidence: 99%
“…This was especially important for the treatment of anti-VEGF unresponsive eyes and those with tachyphylaxis. Numerous investigators have evaluated its efficacy in these circumstances and all demonstrated some benefit [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 ]. Two meta-analyses attempted to evaluate the pooled data from these numerous studies.…”
Section: Exudative Age-related Macular Degenerationmentioning
confidence: 99%
“… 1 As more intravitreal injections are performed, the number of such side effects is also increasing. 1 , 2 Non-infectious IOI has been reported in response to all anti-vascular endothelial growth factor (anti-VEGF) drugs 1 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , triamcinolone 12 , 13 , and ocriplasmin. 14 It typically occurs within a few days after injection, manifesting with visual impairment and vitritis without conjunctival injection and substantial pain.…”
Section: Introductionmentioning
confidence: 99%
“…The third most common cause of blindness (after cataract and glaucoma), age-related macular degeneration (AMD, 8.7% of all blindness), affects the macular region of elderly patients (over 60 years old) [1,2]. Wet AMD is characterized by neovascularization spreading to the subretinal pigment epithelium or subretinal space, and increased presence of intraretinal fluid (IRF) or subretinal fluid (SRF) [3][4][5][6]. AMD is classified as ''wet'' and ''dry'' types [2].…”
Section: Introductionmentioning
confidence: 99%